ANALYSIS OF REGIONS WITH PREVALENCE OF LEPROSY CASES IN THE CITY OF ANÁPOLIS-GOIÁS - Castro, Luísa Campos; Arruda, Jalsi Tacon; Labre, Luciana Vieira Queiroz (CIPEEX, 2025)
Leprosy is a chronic and infectious-contagious disease caused by the agent Mycobacterium leprae. Throughout the centuries, it has been highly stigmatized; however, advances in studies have contributed to a better understanding of this disease, which varies according to its clinical presentation and treatment. This study aims to identify the presence and year of notification of Leprosy in the regions of Anápolis-Goiás from 2019 to 2024, in addition to developing an educational booklet with the main information about the disease, combined with providing data to improve public health programs and policies. This is a quantitative, descriptive, observational, and cross-sectional study, where field research and data collection were carried out in the city of Anápolis, at its Municipal Health Department, in the Dr. Ilion Fleury Jr. health unit, a reference in areas such as viral hepatitis and leprosy. During data analysis, the presence of Leprosy was identified in several regions during the studied period. Those where the disease lasted the longest, with notifications in four of the six years analyzed, were named the regions of Interlandia, Jardim América, Jundiaí, Bairro de Lourdes, and Vila São Joaquim. It is concluded, therefore, that the disease, even after centuries, is still very present, requiring educational strategies for the population so that cure is achieved with adequate treatment, in an attempt to avoid both the dissemination and reactivation of the disease in the body, so that the studied indices decrease more and more over the years.